2022
DOI: 10.1186/s41936-022-00318-2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of zinc oxide nanoparticles (ZnO NPs) on the biology of Galleria mellonella L. (Lepidoptera: Pyralidae)

Abstract: Background Because of its ability to absorb UV radiation and possess catalytic, antibacterial, and semiconducting properties, zinc oxide nanoparticles (ZnO NPs) are increasingly being used in consumer goods. Because nanoparticles are used so often, accurate methods for determining any associated toxicity are crucial. The greater wax moth, Galleria mellonella (L.) (Lepidoptera: Pyralidae) is a suitable experimental model organism due to immune defense of the larvae is very strong. Also, larvae a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
4
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 30 publications
3
4
1
Order By: Relevance
“…The Cd causes retardation in the fifth instar larval growth of L. dispar (Jiang et al, 2020). Our findings showed that in all three generations, pupal weight decreased significantly compared to the control and it was similar to Eskin and Nurullahoğlu (2022) in Galleria mellonella (Lepidoptera: Pyralidae). A tentative answer to this phenomenon could be that the insect facing stress tries to balance the situation, thus spending a high amount of energy which in turn affects the body weight.…”
Section: Discussionsupporting
confidence: 87%
“…The Cd causes retardation in the fifth instar larval growth of L. dispar (Jiang et al, 2020). Our findings showed that in all three generations, pupal weight decreased significantly compared to the control and it was similar to Eskin and Nurullahoğlu (2022) in Galleria mellonella (Lepidoptera: Pyralidae). A tentative answer to this phenomenon could be that the insect facing stress tries to balance the situation, thus spending a high amount of energy which in turn affects the body weight.…”
Section: Discussionsupporting
confidence: 87%
“…Overcoming this stress condition requires a high amount of energy. A similar explanation was suggested by Eskin and Nurullahoğlu (2022) in a study investigating the effect of ZnO-NPs on the pupal weight of Galleria mellonella. Weight decreases in insects treated with ZnO-NPs were also recorded by Pittarate et al, (2021).…”
Section: Effects Of the Tested Nanoparticles On Adult Weights Of B Ge...supporting
confidence: 77%
“…Khooshe-Bast et al (2016) tested ZnO-NPs on Trialeurodes vaporariorum, the LC50 value was 7.35 mg and the mortality rate was 91.6% at 20 mg. Ramadan et al (2020) reported that the latent biological responses of Schistocerca gregaria treated with ZnO were more than that of CuO-NPs. Pittarate et al (2021) and Eskin & Nurullahoğlu (2022) also concluded that ZnO-NPs have toxic effects on Spodoptera frugiperda and Galleria mellonella. Other authors reported the toxic effects of CuO-NPs against different mosquito species (Vivekanandhan et al 2021a, b) and Spodoptera frugiperda (Rahman et al, 2022).…”
Section: Tablementioning
confidence: 99%
“…An in vivo study on Helicoverpa armigera larvae revealed the toxicity of green-synthesised ZnO NPs when using neem leaf extracts at doses up to 200 mg/kg [ 9 ]. Multiple in vivo studies on Galleria mellonella larvae have also reported the toxicity of conventionally synthesised ZnO NPs [ 10 , 11 , 12 , 13 ]. Eskin et al [ 11 ] reported pulpal toxicity at concentrations greater than 1000 mg/kg while observing extended adult longevity at concentrations as high as 5000 mg/kg.…”
Section: Introductionmentioning
confidence: 99%
“…Multiple in vivo studies on Galleria mellonella larvae have also reported the toxicity of conventionally synthesised ZnO NPs [ 10 , 11 , 12 , 13 ]. Eskin et al [ 11 ] reported pulpal toxicity at concentrations greater than 1000 mg/kg while observing extended adult longevity at concentrations as high as 5000 mg/kg. Xu et al [ 12 ] reported toxicity above 400 mg/kg for ZnO nanorods (NRs).…”
Section: Introductionmentioning
confidence: 99%